What is New, Here? Locating an Art Form Within the Western Australian New Music Archive. Issue 3 (3rd July 2017) - Trainer, Adam; Hope, Cat; Green, Lelia
Abstract: The Western Australian New Music Archive seeks to collect documentation of art music activity from Western Australia from 1970 to the present, with the collection materials being made accessible online via a public web portal. Seeking to archive, compile and curate a collection based solely around a particular musical community has required a number of questions to be posed around what actually constitutes new music practice, and specifically, what this practice looks (and sounds) like in the context of Western Australia as the home to the community being represented by this collection. These questions have been answered in part by analysing the collection items themselves, but also through identifying the primary roles of each of the project partners. Tura New Music and the Australian Broadcasting Corporation have contributed content to the collection and the web portal, respectively. Edith Cowan University has had a long tradition of composition and music technology students and staff who have contributed to this community, and leads the research. Finally, as collecting institutions the State Library of Western Australia and the National Library of Australia will retain and provide access to collection materials. Nonetheless, a sufficiently layered and complete analysis of what constitutes new music, and how Western Australian new music practice can be identified, are only possible through analysis of the collection items that is also informed by collection development and its relationship to discourses of art and academia.